THE EFFECT OF LIQUIDITY RATIO ON FINANCIAL PERFORMANCE VIEWED FROM RETURN ON ASSETS (ROA) IN SUB COMPANIES OF CONSTRUCTION AND BUILDING SECTOR LISTED ON THE INDONESIAN STOCK EXCHANGE OF 2016-2020 - Sakti Brata Ismaya; Tia Risnawati; Nurminingsih (Transpublika Publisher, 2023)
The success of a company hinges on the collective performance of its employees. Thus, it becomes imperative for companies to enhance the quality of their workforce's performance. Numerous factors exert influence over employee performance, among them are teamwork, work motivation, and job satisfaction. These factors collectively kindle individuals' commitment towards accomplishing tasks to their fullest potential within the company. This study is conducted to reveal the impact of teamwork, work motivation, and job satisfaction on employee performance, specifically examining the case of the J&T Sibuhuan-Sosa office. Employing an associative research approach with a quantitative methodology, this study encompasses the entire employee population of the Sibuhuan-Sosa J&T office, totaling 30 participants. The analysis employs multiple linear regression via SPSS 22. The findings of the partial analysis reveal that both teamwork and work motivation yield a positive and noteworthy influence on the performance of J&T Sibuhuan-Sosa employees. Conversely, job satisfaction appears to lack significant impact on these employees. Notably, when taken together, teamwork, work motivation, and job satisfaction demonstrate a significant effect on the employees of J&T Sibuhuan-Sosa.